Kegiatan Penapisan Dermatoporosis Pada Populasi Lanjut Usia - Linda Yulianti W; Yohanes Firmansyah; Junius Kurniawan; Farell Christian Gunaidi; Daniel Goh; Margaretha Pramesti Utar (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
The skin, the largest organ in the human body, provides protection against the external environment by covering the entire exterior surface of the body. Dermatoporosis is a skin fragility syndrome that develops as time progresses. Extrinsic and intrinsic factors contribute to skin aging, whereas extrinsic factors comprise nutrition, smoking, ionizing radiation, and solar exposure. In the elderly, the incidence of dermatoporosis is higher. In Europe, the incidence of dermatoporosis varies between 30 and 37%. Dermatoporosis is distinguished by the presence of slender, fragile, and shredded skin. This renders elderly individuals susceptible to complications related to hemorrhaging and infections, thereby exerting a detrimental influence on their overall health and well-being. It is anticipated that by engaging in this exercise, participants will develop a greater understanding of the significance of skin health maintenance.